Molecular Pathogenesis of Infections Caused by Legionella pneumophila - Newton, Hayley J. (American Society for Microbiology (ASM), 2010)
Summary: The genus Legionella contains more than 50 species, of which at least 24 have been associated with human infection. The best-characterized member of the genus, Legionella pneumophila, is the major causative agent of Legionnaires' disease, a severe form of acute pneumonia. L. pneumophila is an intracellular pathogen, and as part of its pathogenesis, the bacteria avoid phagolysosome fusion and replicate within alveolar macrophages and epithelial cells in a vacuole that exhibits many characteristics of the endoplasmic reticulum (ER). The formation of the unusual L. pneumophila vacuole is a feature of its interaction with the host, yet the mechanisms by which the bacteria avoid classical endosome fusion and recruit markers of the ER are incompletely understood. Here we review the factors that contribute to the ability of L. pneumophila to infect and replicate in human cells and amoebae with an emphasis on proteins that are secreted by the bacteria into the Legionella vacuole and/or the host cell. Many of these factors undermine eukaryotic trafficking and signaling pathways by acting as functional and, in some cases, structural mimics of eukaryotic proteins. We discuss the consequences of this mimicry for the biology of the infected cell and also for immune responses to L. pneumophila infection.